Effect of pH Value and Dispersant on Dispersibility of Silica Ceramic Slurry - Liu, Li; Xu, Haiyan; Wu, Guotian (Asian Journal of Chemistry, 2014)
In present work, the effect of pH value and the dosage of the dispersing agent on stability and dispersibility were evaluated. Sodium poly-carboxylic acid was used as a dispersing medium for silica porous ceramic slurry. The stabilization mechanism of this kind of anion polymer polyelectrolyte in the slurries is attributable to the enhanced the effect of the electrostatic repulsion and the stereo hindrance and the zeta potential can get the highest value of 42.5 mV in addition of 0.06 % at pH = 9 in the silica ceramic slurry.